2019
DOI: 10.1136/tobaccocontrol-2018-054837
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nations meeting the MPOWER targets between 2014 and 2016: an update

Abstract: ObjectiveSince the WHO released the Monitoring tobacco use and tobacco control policies; Protecting from the dangers of tobacco smoke; Offering help to quit tobacco; Warning the public about the dangers; Enforcing bans on advertising, promotion and sponsorship; and Raising tobacco taxes (MPOWER) policy package to assist nations with implementing the Framework Convention on Tobacco Control (FCTC), 88 countries have adopted at least one MPOWER policy at the highest level as of 2014. Building on previous evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(64 citation statements)
references
References 26 publications
(35 reference statements)
2
60
1
Order By: Relevance
“…Specifically, an analysis of GATS data from several developing countries, including Indonesia, Malaysia, Thailand, and Vietnam, showed that large pictorial warnings were associated with a lower cigarette smoking prevalence, particularly among those who had a lower level of education [ 13 ]. It is estimated that, among the MPOWER measures, health warnings contribute to preventing the largest number of smoking-attributable deaths (13.3 million, compared to <1 million for each of the other MPOWER policies) [ 14 ]. Therefore, the Lao NTCC should continue these efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, an analysis of GATS data from several developing countries, including Indonesia, Malaysia, Thailand, and Vietnam, showed that large pictorial warnings were associated with a lower cigarette smoking prevalence, particularly among those who had a lower level of education [ 13 ]. It is estimated that, among the MPOWER measures, health warnings contribute to preventing the largest number of smoking-attributable deaths (13.3 million, compared to <1 million for each of the other MPOWER policies) [ 14 ]. Therefore, the Lao NTCC should continue these efforts.…”
Section: Discussionmentioning
confidence: 99%
“…These measures include: Monitoring tobacco use and tobacco control measures (Article 20); Protecting people from tobacco smoke (Article 8); Offering help to quit tobacco (Article 14); Warning people about the dangers of tobacco (Articles 11 and 12); Enforcing bans on tobacco advertising, promotion and sponsorship (Article 13); and Raising tobacco taxes (Article 6) [ 18 , 19 ]. Despite an accelerating impact of MPOWER policies, the implementation of legislation related to tobacco advertising at a global level is still limited [ 20 , 21 , 22 ]; moreover, scarcity of quality information at a country-level, lobbying, and constituency building from the tobacco industry have delayed the implementation and enforcement of these measures in Latin America [ 23 , 24 ]. In the group of studied countries, Peru and Bolivia have the minimum level of implementation; Argentina and Mexico are in an intermediate level of implementation with a ban of advertising on national television, radio, print media, and some direct or indirect forms of advertising, and although Colombia, Brazil, and Chile have the maximum level of implementation with a comprehensive ban of all forms of advertising, there is still room for improvement in the compliance of measures [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estimation of the prevalence of cigarettes smoking showed a decline from 33.3% in 2000 to 20.9% in 2025 (World Health Organization, 2019). This effect might be due to various strategies for tobacco prevention programs, promoting smoking cessation, and enhanced public awareness concerning the harmful effects of smoking and SHS exposure (Levy et al, 2020). As noted, promoting smoking cessation is the one of those strategies to help a smoker quit smoking or to reduce cigarettes consumption.…”
Section: Introductionmentioning
confidence: 99%